THE IMPORTANCE OF MOTIVATION AND SELF-CONTROL SKILLS IN MANAGING PRE-COMPETITION STRESS AMONG WKF KARATE ATHLETES (World Bulletin of Physical Education and Sports Science, 2026)
This article examines the importance of motivation and self-control skills in managing pre-competition stress among WKF karate athletes. In modern karate, competitive success depends not only on physical fitness, technical mastery, tactical preparation, and combat experience, but also on the athlete’s ability to regulate emotional tension before and during competition. Pre-competition stress may appear through anxiety, excessive excitement, fear of failure, decreased confidence, muscle tension, and unstable concentration. These psychological states can negatively affect reaction speed, tactical decision-making, accuracy of techniques, and overall competitive performance. At the same time, properly directed motivation and developed self-control skills can transform stress into a mobilizing factor that increases readiness, discipline, and confidence. The article highlights the pedagogical and psychological role of motivation, goal orientation, emotional regulation, self-observation, breathing control, and positive self-instruction in preparing WKF karate athletes for competition. Special attention is given to the role of the coach as a pedagogical leader who creates a psychologically supportive training environment and helps athletes develop resilience, self-confidence, and stable competitive behavior.
Keywords: WKF karate, pre-competition stress, motivation, self-control, psychological preparation, emotional regulation, competitive performance, confidence, sports psychology, pedagogical support.